2018
DOI: 10.1080/03054985.2018.1409973
|View full text |Cite
|
Sign up to set email alerts
|

The role of schools in explaining individuals’ subject choices at age 14

Abstract: The subjects that young people study from age 14 onwards may have important consequences for their future academic and labour market outcomes. These decisions are shaped by the schools in which they find themselves. Schools also face constraints of their own. This paper explores the extent to which individuals' decisions are affected by the school they attend and to what extent this is affected by the composition of schools in terms of academic attainment, gender, and socioeconomic background. We use multi-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The United Kingdom education system is prone to bifurcating students along either a science or humanities path from an early age, sometimes as young as 13 [1]. If sufficiently motivated, it is possible to rediversify at most stages, but on the whole, these early choices influence the course of entire careers, and anecdotally, it is rare to find people equally open-minded about science and arts.…”
Section: Introductionmentioning
confidence: 99%
“…The United Kingdom education system is prone to bifurcating students along either a science or humanities path from an early age, sometimes as young as 13 [1]. If sufficiently motivated, it is possible to rediversify at most stages, but on the whole, these early choices influence the course of entire careers, and anecdotally, it is rare to find people equally open-minded about science and arts.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent study, Anders et al . () highlighted the role that schools play in many subject choice decisions. They suggested that schools’ actions are often strongly associated with school characteristics, such as the composition of school intake in terms of academic attainment and socio‐economic status of pupils’ families, which impose constraints on what subjects can be viably offered by schools (ibid.).…”
Section: Background and Contextmentioning
confidence: 99%
“…There is also a link between the social and ability compositions of school intake and subject choices of pupils (e.g. Anders et al ., ). Moreover, school characteristics affect subject choices too and, even after accounting for family background and academic ability, young people who attend schools with higher proportions of pupils from disadvantaged socio‐economic background are less likely to select academic subjects than those who attend schools with more advantageous social composition of their intake (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Institutional constraints are likely to be one factor determining students' curriculum 'choices' , and there is evidence that schools that performed badly on the raw five+ GCSE grade A*-C measure moved most rapidly towards vocational courses and made the most substantial gains as a result (Jin, Muriel, & Sibieta, 2011). Other papers in this Special Issue suggest that pupils' choices may be shaped by their school (Anders, Henderson, Moulton, & Sullivan, 2018;Barrance & Elwood, 2018;Smyth, 2018).…”
Section: Introductionmentioning
confidence: 99%